Consequences of low birth weight, maternal illiteracy and poor access to medical care in rural India: infantile iatrogenic Cushing syndrome. (21st August 2015) - Karande, Sunil
Abstract : Home delivery, low birth weight babies and maternal illiteracy among the poor in rural India are frequent. The rural poor prefer to seek healthcare from private providers,  most of whom have no formal medical training and buy medicines from private pharmacies without a prescription owing to a weakly regulated environment. This report is of a 4-month-old baby from a remote village in northern India, who presented with exogenous Cushing syndrome. This baby was a full-term low birth weight home delivery. As the baby was not growing well, treatment was started at 1 month by a private doctor with betamethasone drops The mother on her own volition continued giving the betamethasone drops by buying the medicine over the counter from a private pharmacy. This case highlights the gaps in essential health services in rural India and the steps being taken to improve the situation.